2017
DOI: 10.1111/hepr.12867
|View full text |Cite
|
Sign up to set email alerts
|

ITPA gene variation and ribavirin‐induced anemia in patients with genotype 2 chronic hepatitis C treated with sofosbuvir plus ribavirin

Abstract: Patients with the ITPA CA/AA genotype were less likely to develop anemia than those with the ITPA CC genotype and were more likely to complete SOF/RBV therapy. These results may provide a valuable pharmacogenetic diagnostic tool to predict drug-induced adverse events, particularly in patients with pre-existing anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The role of RBV adherence might affect SVR. Japanese real‐world data on the efficacy of SOF + RBV for genotype 2 infections have been reported, and there is disagreement on the impact of RBV dose reduction on SVR …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of RBV adherence might affect SVR. Japanese real‐world data on the efficacy of SOF + RBV for genotype 2 infections have been reported, and there is disagreement on the impact of RBV dose reduction on SVR …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The role of RBV adherence might affect SVR. Japanese real-world data on the efficacy of SOF + RBV for genotype 2 infections have been reported, [12][13][14][15] and there is disagreement on the impact of RBV dose reduction on SVR. 12,13 The goal of antiviral treatment is to avoid fibrosis progression by HCV eradication and to prevent hepatic decompensation or hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still few reports on patients treated with IFN‐free DAA therapy, and factors associated with RBV‐induced hemolytic anemia have not been examined in detail. A previous report suggested that ITPA was associated with RBV‐induced anemia in patients during treatment with SOF/RBV therapy, but other factors were unknown . This study identified groups that did not develop anemia with SOF and RBV combination treatment in HCV genotype 2‐infected patients.…”
Section: Discussionmentioning
confidence: 76%
“…Japanese patients with the rs1127354 CC genotype are prone to developing severe anemia during treatment with a combination of PEG‐IFN plus RBV . The ITPA SNPs have also been shown to be among significant factors associated with anemia in patients during treatment with PEG‐IFN/RBV plus telaprevir or simeprevir triple therapy and SOF/RBV . However, factors associated with RBV‐induced hemolytic anemia other than ITPA in patients with SOF/RBV therapy have not been examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Insofar as IFNL3 (IL28B) influences the responsiveness to PEG‐IFN and RBV, polymorphisms in ITPA gene—the most studied gene in our data mining—influence anaemia induced by RBV and strongly correlated to RBV‐induced haemolytic anaemia (RIHA) . The development of RIHA during anti‐HCV treatment is responsible for treatment discontinuation, dose reduction, and consequently decreased SVR.…”
Section: Discussionmentioning
confidence: 99%